Socio-Cultural Factors in Family Independence Prevent the Transmission of Leprosy in Sampang, Madura Island. (Medico Legal Update, 2020)
Introduction: Leprosy is an infectious disease that causes various problems, not only in medical terms butalso extends to social, economic, cultural, security and social security issues. Efforts made to break the chainof transmission of leprosy cases focus more on individuals who have not focused on families that have ahigh transmission chain.Purpose: The research aims to explore the social factors of social and cultural factors in influencing familyindependence in preventing transmission of leprosy, describing the independence of the family in preventingtransmission of leprosy, then compiled an example of a culture-based family independence program modelfor the prevention of leprosy transmission in Sampang with a theoretical approach used namely FamilyCentered Nursing and the theory of Transcultural Nursing in the form of modules.Method: This study uses a qualitative research approach. Data saturation until five participants were obtainedwho carried out data retrieval in an in-depth interview. Data analysis using the Collaizi analysis method.Results: Identification found four main themes: ((1) Religious; (2) Social Factors; (3) Economic Factors;and (4) Cultural Value. Conclusions: The description of the independence of families who care for lepers isstill influenced by many factors, especially tradition and culture, efforts to break the chain of transmissionare also closely related to care efforts that still do not reflect preventive values.